Quantum-Chemistry Based Design of Halobenzene Derivatives With Augmented Affinities for the HIV-1 Viral G4/C16 Base-Pair - El Darazi, Perla; El Khoury, Léa; El Hage, Krystel; Maroun, Richard G.; Hobaika, Zeina; Piquemal, Jean-Philip; Gresh, Nohad (Frontiers in Chemistry, 2020)
The HIV-1 integrase (IN) is a major target for the design of novel anti-HIV inhibitors. Among these, three inhibitors which embody a halobenzene ring derivative (HR) in their structures are presently used in the clinics. High-resolution X-ray crystallography of the complexes of the IN-viral DNA transient complex bound to each of the three inhibitors showed in all cases the HR ring to interact within a confined zone of the viral DNA, limited to the highly conserved 5’CpA 3’/5’TpG 3’ step. The extension of its extracyclic CX bond is electron-depleted, owing to the existence of the ‘sigma-hole’. It interacts favorably with the electron-rich rings of base G4. We have sought to increase the affinity of HR derivatives for the G4/C16 base pair. We thus designed thirteen novel derivatives and computed their Quantum Chemistry intermolecular interaction energies, E (QC), with this base-pair. Most compounds had deltaE (QC) values significantly more favorable than those of the HR of the most potent halobenzene drug presently used in the clinics, Dolutegravir. This should enable the improvement in a modular piece-wise fashion, the affinities of halogenated inhibitors for viral DNA (vDNA). In view of large scale polarizable molecular dynamics simulations on the entirety of the IN-vDNA-inhibitor complexes, validations of the SIBFA polarizable method are also reported, in which the evolution of each deltaE(SIBFA) contribution is compared to its QC counterpart along this series of derivatives.